Language Learning Strategies in English Language Learning: A Survey Study - Astri Hapsari (Universitas Negeri Yogyakarta, 2019)
Strategic competence involves a number of learning and communication strategies which can be learned by language learners. These behaviors and thinking process can help second language learners to accelerate their target language learning. Teachers’ knowledge on these strategies will help language learners in overcoming the problems of their learning process. This survey study aims to describe students’ profile of strategic competence by mapping their language learning strategies. The participants were 106 students of Department of English Language Education in academic year 2014/2015. The instrument used was Oxford’s (1989) Strategy Inventory for Language Learning (SILL) Worksheet, Version 7.0 for Speakers of Other Languages Learning English. Students’ profile of strategic competence in academic year 2014/2015 is: memory strategy (3.20), affective strategy (3.38), cognitive strategy (3.45), compensation strategy (3.46), social strategy (3.46), and metacognitive strategy (3.63). Therefore, the only strategy who has achieved high profile is metacognitive strategy (3.63). The other strategies are still on medium profile, which means all the students sometimes use the strategies. For the whole SILL strategies, students of Department of English Language Education, Universitas Islam Indonesia in academic year 2014/2015 get mean score 3.43, which also means on medium profile of strategic competence. From the result, it is recommended that the students need to develop the other five strategies from medium to high profile. Keywords: strategic competence, language learning strategies, survey study